Wharton’s jelly-derived mesenchymal stem cells ameliorate high altitude-induced heart injury by promoting type 2 macrophage polarization via COX2-PGE2 pathway - Zhang, Wenhong; Zhao, Li; Cui, Jing; Zhang, Yan; Li, Dongtao; Hong, Zhibo; Liu, Jiamin; Wang, Shan; Zhang, Ningkun; Li, Yang; Chen, Yu (Frontiers in Immunology, 2025)
BackgroundChronic high-altitude hypobaric hypoxia leads to high-altitude heart disease and heart failure. Recent research has indicated that WJMSCs (Wharton’s jelly-derived mesenchymal stem cells, WJMSCs) can alleviate ischemic myocardial injury and improve cardiac dysfunction, and macrophage polarization may have been involved. However, few studies have focused on the cardioprotective effects of WJMSCs against HAHI (high-altitude-induced heart injury, HAHI). Here, our research focused on how WJMSCs regulate macrophage polarization impacted myocardial repair in HAHI.MethodsC57/BL6J mice were fed for 28 days at a hypobaric chamber that had a comparable altitude of 6000 m, and WJMSCs were injected intravenously before HH (hypobaric hypoxia, HH) exposure. To assess cardiac function, echocardiography was carried out. Blood and heart tissue were collected for subsequent analysis. We simulated anoxic environment in vitro by inducing BMDMs (bone marrow-derived macrophages, BMDMs) with 1% O2, and employed co-culture system to investigate how WJMSCs affect macrophage polarization.ResultsAbnormal myocardial fibrosis and cardiomyocyte apoptosis, cardiac inflammation and dysfunction were exhibited in the Chronic HAHI mouse model. WJMSCs infusion maintained the cardiac structure and function in HAHI mice. Furthermore, WJMSCs infusion was effective in elevating the M2 macrophages proportion and decreasing inflammation in the heart. In vitro studies revealed that hypoxia stimulation elevated the ratio of M1 macrophages in comparison to those in the Control group and coculturing with WJMSCs encouraged the shift of M1 to M2 macrophages. Surprisingly, the anti-inflammatory effects of WJMSCs on M2 polarization were negated with pretreatment of a COX2 (Cyclooxygenase-2, COX2) inhibitor, which could be reversed with PGE2 (prostaglandin E2, PGE2) addition.ConclusionsIn conclusions, our findings indicated that WJMSCs infusions may enhance M2 macrophage polarization through the COX2-PGE2 pathway, and therefore safeguard against cardiac damage in HAHI mice.